(untitled) (Journal on studies and research of academic knowledge, 2024)
Nitrogen is a nutrient that can directly influence wheat crop yield. In the search for a more sustainable production, the purpose of this study was to evaluate the response of wheat to inoculation with Azospirillum brasilense in combination with applied nitrogen in different phenological stages. The experiment was carried out in the IPTA experimental field, located in Ybyrarobaná, Canindeyú, Paraguay. A randomized complete block design was used with a 2 x 3 bifactorial arrangement and two controls (without inoculation and without nitrogen fertilization; with inoculation and without nitrogen fertilization). The factors were the absence and application of A. brasilense and the application of nitrogenous fertilizer in: tillering; tillering and elongation; tillering and heading. The variables evaluated were plant height (PH), number of spikes per m2 (NS), yield (Y), thousand grain weight (TGW) and hectoliter weight of grains (HW). The data were subjected to analysis of variance and the means were compared by Tukey’s test at 5%. The application of A. brasilense in wheat associated with nitrogen in three phenological stages did not present statistical difference in the variables PH, NS, Y and TGW. On the other hand, a significant difference was observed in the factorial arrangement. The PH, the application of nitrogen in the tillering and tassel phenological stages, as well as the association of the inoculation with the application of nitrogen at the moment of tillering and divided in the tillering and elongation, showed superior results, however, not differing from the controls.